The Gonium pectorale genome demonstrates co-option of cell cycle regulation during the evolution of multicellularity - Erik R. Hanschen (Nature Portfolio, 2016)
The undifferentiated Gonium pectorale represents the initial transition to multicellularity. Here, Bradley Olson, Erik Hanschen and colleagues describe the genome of Gonium pectorale, demonstrating that co-option of the retinoblastoma cell cycle regulatory pathway was a key genetic change in the evolution of multicellularity.